Pendampingan Guru Madrasah dalam Pendayagunaan Learning Management System Moodle - Maisyaroh, Maisyaroh; Ulfatin, Nurul; Juharyanto, Juharyanto; Prestiadi, Dedi; Ariyanti, Nova Syafira; Saputra, Bagus Rachmad; Adha, Maulana Amirul; Sjaifullah, Farid Wadjdi (Department of Accounting, Faculty of Business and Economics, Universitas Islam Indonesia, 2023)
The community service conducted aims to contribute to our partner school, MTs Sunan Kalijogo in Malang City, by providing support for teachers' skills through the utilization of the Learning Management System (LMS) Moodle as a tool for remote learning during the pandemic. The implementation methods include mentoring, training, and workshops. The stages carried out are: (1) preparation, (2) training and workshops, (3) implementation of the results, and (4) evaluation. The results of the community service are as follows: (1) 90% of the participants strongly agree that the use of the Moodle program can assist teachers in conducting online education in the madrasah; (2) 80% of the participants are highly proficient in utilizing the Moodle program for distance learning; and (3) Based on the reflections conducted, participants have gained a strong understanding of using Moodle in the context of online education during the pandemic. This is evident in the high level of interest and enthusiasm displayed by the participants.